(untitled) (Communications in Mathematical Research, 2019)
The aim of this paper is to establish the Fekete-Szegö inequality for a subclass of bi-univalent strongly quasi-starlike functions which is defined in the open unit disk. Furthermore, the coefficients a_2 and a_3 for functions in this new subclass are estimated.